Frequency Reconfıgurable Lıbra Shape Antenna for mmW 5 g Communıcatıons - Gozek, Emine Ceren; Tokan, Fikret; Karaaslan, Muharrem (SPRINGER, 2025)
A frequency reconfigurable Libra shape antenna has been presented to provide frequency reconfigurability. Two PIN diodes are integrated into the designed antenna structure thus the antenna is operated in four different modes. Each mode is characterized by specific resonant frequencies, reflection coefficients (S11\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$${S}_{11}$$\end{document}), and bandwidths, demonstrating the reconfigurability of the antenna. Between 26 and 40 GHz, the S11\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$${S}_{11}$$\end{document} values for the different modes of the antenna are below - 10 dB, indicating the usability of the antenna in this frequency range. The proposed structure has been fabricated with a printed circuit device and tested with a vector network analyzer in the microwave laboratory. The experimental results support the simulation results and confirm that the antenna can maintain optimum performance in the specified frequency ranges. The developed multimode antenna structure is a good candidate for various applications such as telecommunications (5G), satellite communication systems, scientific research, Radio Astronomy, Industrial and Medical Applications and radar systems.
Keywords: 5G antennas; Reconfigurable antenna; Mm-Wave; PIN diode; 28 GHz communication; 38 GHz communication; MONOPOLE ANTENNA; BAND; DESIGN; Engineering; Optics; Physics